Circulating metabolites and fatty acids associated with ultra-processed food consumption: results from the EPIC study - Jessica Blanco-Lopez; Sahar Yammine; Joseph A. Rothwell; Mathilde His; Carine Biessy; Pekka Keski-Rahkonen; Bernadette Chimera; Inarie Jacobs; Aline Al Nahas; Emine Koc Cakmak; Oliver Robinson; Fernanda Morales Berstein; et al. (Critical Reviews in Food Science and Nutrition, 2026)

Intracellular Amorphous Calcium Carbonate Biomineralization in Methanotrophic Gammaproteobacteria Was Acquired by Horizontal Gene Transfer From Cyanobacteria - Karim Benzerara; Maxime Millet; Fériel Skouri‐Panet; Geoffroy Gaschignard; Neha Mehta; Malo Bezard; Géraldine Caumes; Daniel M. Chevrier; Manuela Dezi; Arnaud Duverger; Jean‐Michel Guigner; Ana Gutiérrez‐Preciado; et al. (Environmental Microbiology, 2026)
Some bacteria genetically control the biomineralisation of intracellular amorphous calcium carbonates (iACC) with potential implications for microbial physiology, evolution, bioremediation and biogeochemical cycling. Until now, this capacity has been documented in Cyanobacteria , the giant gammaproteobacterium Achromatium and a few magnetotactic Pseudomonadota and Nitrospirota . Here, we report the discovery of iACC biomineralisation in members of the Methylococcaceae , a family of aerobic methanotrophic Gammaproteobacteria . A homologue of the ccyA gene, a diagnostic marker for iACC formation in Cyanobacteria , was identified in several Methylococcaceae genomes, based on the conserved C‐terminal (GlyZip)3 domain of the encoded calcyanin protein. Moreover, two cultivated strains, Methylococcus geothermalis and Methylococcus mesophilus , whose genomes contained the ccyA gene, were consistently shown to form iACC. The ccyA genes of Methylococcaceae and Microcystis share higher sequence similarity than with other Cyanobacteria , suggesting horizontal gene transfer (HGT) from an ancestral Microcystis ‐like cyanobacterium to Methylococcaceae . This finding extends the known taxonomic distribution of ccyA and suggests that the capability to biomineralize iACC was acquired by HGT. The discovery of iACC in methane‐oxidising Methylococcaceae highlights a previously unrecognised coupling between calcium carbonate biomineralisation and methane cycling in aquatic environments, suggesting an overlooked role of iACC formation in microbial carbon storage and local geochemical regulation.